Understanding voluntary disclosure: Malaysian perspective - Zaini Embong, (Fakulti Ekonomi dan Pengurusan, 2014)
This study investigates voluntary disclosure made by Malaysian firms. Unlike previous researches that identify the antecedents and/or consequences of disclosure, this study examines the disclosure in more detail, in terms of what items are disclosed as well as the trend of disclosure over the years of study. The main purpose of doing this is to better understand the disclosure behavior of firms. Better understanding of the firms’ disclosure behavior can lead to a more appropriate research on disclosure especially on how to motivate firms to disclosure more. Annual reports of 156 firms listed on main board of Bursa Malaysia from year 2006 to 2010 are analyzed. A checklist containing 49 items are used to measure the voluntary disclosure level of these firms. The score is given based on items disclosed in the annual report. Contradict to claim by previous studies that disclosure is a sticky policy, the results of this study show that there is an increasing pattern in disclosure level. In support of proprietary cost argument, the results show that information of strategic nature is disclosed less compared to financial information. This study differs from previous studies by focusing in detail on the items disclosed by firms instead of identifying factors or consequences of the disclosure. The trend of disclosure is determined by having a constant sample throughout the study period of five years. The results of this study raise several questions that can be a subject for future research.